Analisis Perbandingan Forecasting Demand Limestone Plant 9 Menggunakan Metode Time Series - Helda Yuana Arientantri Prastari Prastari; Rahmaniyah Dwi Astuti (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
PT Indocement Tunggal Prakarsa Tbk is one of the largest cement producers in Indonesia and has been established since 1975 with a production capacity of 4.3 million tons per year, this aims to meet the demand for cement needed by the Indonesian people. This study aims to forecast the demand for limestone raw materials at PT Indocement Tunggal Prakarsa Tbk Plant Cirebon. The data used is limestone raw material demand data from January 2023 to December 2023. The Time Series method is an analysis method to make a forecast needed in the future. The variables used in this study are the demand for limestone raw materials in a certain period as a bound variable and the time period (months) as an independent variable. There are three types of method models used in this study, namely the Moving Average Method, Exponential Smoothing, and Trend Analysis. The error rate in the forecasting results was tested using the results of the mean absolute percentage error (MAPE) value. Based on the results of the MAPE calculation that has been obtained as the best limestone raw material demand forecasting model, namely by using the Trend Analysis method because the method has the smallest forecasting error rate, which is 30.832%.